Proudly Peripheral. (2nd October 2019) - Sørensen, Tonje Haugland
Abstract : This article explores the relationship between center and periphery within Norwegian art at the turn of the century. It focuses on the Holmenkollen tourist hotel in Christiania (present-day Oslo) and the artists and architects involved in its construction. It shows how the relationship between the center/periphery is one of dynamic encounter and one where the relations of power are much more flexible than the traditional notion of the center dictating the terms. Moreover, it highlights how Norwegian artists through their work and writing reflected on their role as belonging to a peripheral art nation and illustrates how they found ways to make this peripheral identity a well of artistic creativity and the base for an artistic pride.